Teacher Teaching Skills at Melaka suburban Secondary School : A Research Gap from Literature Perspective - Saleh, Hasan; Nur Afiqah Khumairah Abd Karim (Journal of TVET and Technology Review, 2026)
This study examines the relationships between student engagement, student motivation, student learning environment, and technology access in shaping teaching skills among teachers in suburban secondary schools in Melaka, Malaysia. Despite national initiatives aimed at digital transformation in education, disparities in technological access and pedagogical readiness continue to challenge teachers in under-resourced school contexts. The findings provide empirical evidence on how psychological, pedagogical, and technological factors collectively influence teachers’ teaching skills. This study contributes to the existing literature by offering a teacher-centred and context-sensitive perspective, providing insights to inform more inclusive educational policies and targeted professional development initiatives.